Corporate Governance, Ownership and Profit Productivity Change: Evidence from Universal Banks in Ghana - Gogovie, F.K. (University of Ghana, 2019)
Corporate governance generally look at the financial, market and efficiency performance of banks, however this study attempts to focus on bank productivity and corporate governance. The current study identifies the effect of corporate governance on bank productivity change of foreign-owned and domestic banks. The study adopts the nonparametric DEA-based Luenberger productivity indicator by Chamber, Chung and Fare (1996) to estimate bank productivity of twenty nine universal banks in Ghana from 2000 to 2014. Furthermore, the Spearman’s correlation analysis is employed to identify the source of bank productivity. The SZAL test is used to compare the distribution of bank productivity of foreign-owned and domestic banks. Finally, panel regression models are employed in determining how governance affects dynamic productivity of banks. The results indicate that, productivity change of banks in Ghana, which averaged 1.37 percent over the study period was driven significantly by profit technological change. However, the competing bank ownership theories and hypotheses are not supported because the differences of productivity, technological and efficiency changes not significant. Corporate governance has significant effect on bank productivity for both foreign-owned and domestic banks in Ghana in the observed period. Whereas board size and executive compensation significantly have negative effects on bank productivity after controlling for bank size, leverage, profitability and sales growth. Therefore, the study lends support for the agency theory and the resource dependence theory.
MPhil. Finance
Keywords: Corporate Governance; Bank Productivity; Banking Industry